AGENDA SETTING BY THE MALAY ONLINE NEWSPAPERS DURING THE SEMENYIH BY-ELECTION - Mohamed, Shafizan; Abdul Manan, Kamaruzzaman (2019)
Media can play an important role in the public's voting decision. In Malaysia, Facebook the one of the most popular social media used in political communication. In relation, this paper investigates whether online news shared on Facebook set the political agenda for its readers. The Semenyih by-election offered an interesting case to study this relationship. In response to the importance of social networking sites as sources of information, news media organizations have set up Facebook channels in which they publish news stories or links to articles. This allows for wider news reach as well as audience participation. When audience members read and subsequently comment on news articles on Facebook, it becomes possible to identify public opinions and sentiments on the issues being covered. Content analysis was done on 300 issues highlighted by two Malay online news Facebook pages namely Malaysiakini BM and Sinar Harian during the Semenyih by-election. A total of 691 user issues were sampled to investigate whether user issues mirror the issues and sentiments presented in the news articles. The descriptive findings showed that news sentiments and audience sentiments are almost similar but did not exactly match.